EXPLORING ENGLISH LECTURERS’ BELIEFS ABOUT THE USE OF NATIVE LANGUAGE IN THE EFL CONTEXT - Muhammad Hidayat; Gunadi Hari Sulistyo (Jurnal Pendidikan Humaniora, 2020)
Abstract: The beginning of the twentieth century was the time when the ELT theoreticians and academics prohibited the use of mother tongue with the assumption that teaching and learning a new language in the exclusive and monolingual approach must be better-off. After obtaining its dominance in language teaching methodology, this monolingual approach began to be questioned. Moreover, what is up-to-date in works of literature and theories is not essentially indicating what actually arrives on the scene in the EFL classroom practices. The students' own-language (OL) has survived over the years. This research explored the lecturers' beliefs about the use of own-language by focusing on certain variables in the context of EFL. The findings clearly provide shreds of evidence that their beliefs about own-language, particularly in their classroom practices, are more complicated than generally presented in the ELT literature. Subsequently, the results could offer a description of how the lecturers use the own-language based on their own beliefs. The report also confirms that own-language is unavoidable and becomes a part of new language learning. Lastly, some considerations for ELT teachers, lecturers, and further researchers are provided at the end of the discussions.Key words: native language use, lecturers’ beliefs, EFL context Abstrak:Awal abad kedua puluh adalah saat dimana para ahli teori dan akademisi pengajaran Bahasa Inggris melarang penggunaan bahasa ibu dengan asumsi bahwa bahasa baru harus diajarkan dan dipelajari secara eksklusif dan dengan satu bahasa. Setelah memperoleh dominasinya dalam metodologi pengajaran bahasa, pendekatan monolingual ini mulai dipertanyakan. Selain itu, apa yang terbaru dalam literatur dan teori tidak serta merta mencerminkan apa yang sebenarnya terjadi dalam praktik kelas Bahasa Inggris. Kenyataannya, bahasa sendiri telah bertahan selama bertahun-tahun. Penelitian ini mengeksplorasi kepercayaan dosen tentang penggunaan bahasa sendiri dengan berfokus pada variabel-variabel tertentu dalam konteks Pengajaran Bahasa Inggris. Temuan dari penelitian ini jelas membuktikan bahwa kepercayaan mereka tentang bahasa sendiri, khususnya dalam praktik kelas, lebih rumit daripada yang umumnya disajikan dalam literatur pengajaran Bahasa Inggris. Selanjutnya, hasil penelitian ini menyajikan deskripsi tentang bagaimana umumnya para dosen menggunakan bahasa sendiri berdasarkan kepercayaan mereka. Laporan penelitian ini juga menegaskan bahwa bahasa sendiri tidak dapat dihindari dan bahkan menjadi bagian dari pembelajaran sebuah bahasa baru. Terakhir, beberapa pertimbangan untuk guru, dosen, dan peneliti selanjutnya dalam dunia pengajaran Bahasa Inggris disediakan di bagian akhir diskusi.Kata kunci: bahasa ibu, persepsi dosen, konteks EFL